Analisis Aspek Ergonomi Pada Aktivitas Penangkapan Ikan di Kapal - Cici Rahayu Damanik; Susilawati S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Ergonomics is a branch of science that systematically utilizes information about human nature, abilities and limitations to design a better work system. In fishing operations, ergonomics is closely related to work comfort and safety on board. The aim of this research is to describe fishing activities on board and to analyze ergonomic aspects of fishing activities. This research is a Literature Review research. Data processing in this study uses the REBA (Rapid Entire Body Assessment) method and JSA (Job Safety Analysis) activities. This method is intended to observe in detail the activities, the equipment used, how it works and the layout on the boat. The results of research on fishing gear and assistive devices on board are not ergonomic because the steering wheel seat has no backrest and is too far from the steering levers and levers. gas; the condition of the crew rest room and the helmsman is not proper; noise in the engine room area due to the sound of ship engines; smoke from the ship's exhaust hitting the helmsman; fishing gear operating equipment is still done manually; fishermen's working position is still very high risk of accidents and muscle complaints.